High tech, high touch : library customer service through technology - Jurewicz, Lynn (American Library Association, 2003)
Ever-expanding technologies are raising the bar, as customers increasingly expect fast, sophisticated solutions and results in their interactions with the library. Drawing on their system of improved customer service available through technology, the authors show how automating traditional library services can decrease staff workloads while improving speed and access for customers. Real-life lessons and visual examples from libraries who have implemented these systems provide a customizable model for your library to achieve the same goals-from offering virtual library cards to online registration for library programs. High Tech, High Touch illustrates technical solutions that really work, inspired by effective customer service strategies used by businesses. These are unique technology solutions-based on digital libraries, portals, e-mail notifications, and database interfaces to the Web-to solve everyday public library problems. Supported by narrative descriptions and screen shots, this is a springboard for designing customized library systems that address unique local service issues. Library directors, branch managers, and department heads can automate the most tedious library tasks while improving customer service and saving staff time.